Healing the nations - Dortzbach, Karl (Verbum et ecclesia, 2004)
This article gives the motivations, methodology and some results of a study done in Christian healing interventions in African contexts of stress and violence. Healing in community has been viewed through the prism of "shalom". Shalom occurs when people who are in a right relationship with God and each other enjoy and share together the resources of the earth in ways that show Christ is Lord of all creation. Charts are given showing the various kinds of community needs, ways to intervene, and some indications of ways to evaluate the interventions.